Pulsed electric field enhanced Bacillus sp. DL4 biodegradation of triclosan focusing on operational performance and metabolomic analysis - Li, Xuejie (Environmental technology, 2024)
Electrochemical-assisted microbial degradation technology was considered a crucial strategy to reduce micropollutants, but the mechanism of the pulsed electric field (PEF) in affecting biodegradation had not been systematically studied. This study aimed to construct a bio-electrochemical system (BES) using PEF to investigate its effect on the degradation of triclosan (TCS) by the aerobic bacterium Bacillus sp. DL4. The operating optimal parameters for the BES (i.e. 0.01 A of the pulsed current, 1000 Hz of the pulse frequency, Fe (+)-C (-) of the plate materials, 4 cm of the plate spacing) were obtained by batch experiments. The maximum biomass (OD600 = 1.0 ± 0.05) was achieved and the removal efficiency of TCS reached above 95% in 24 h under the obtained operating conditions. Meanwhile, a thorough and methodical investigation of the metabolites in strain DL4 stimulated by PEF using untargeted Liquid Chromatography - Mass Spectrometry (LC-MS). In multivariate analysis, the experimental groups showed a notable separation in Principal Components Analysis (PCA) and Orthogonal Partial Least Squares Analysis discriminant analysis (OPLS-DA) score plots. A total of 3181 differential metabolites were obtained, and the up-regulated metabolites were mainly related to 'Aminoacyl-tRNA biosynthesis', 'Arginine and proline metabolism', 'Lysine degradation', 'ABC transporters', and 'TCA cycle', implying that PEF enhanced the degradation efficiency of TCS by enriching functional genes with transport ability and ion migration ability in cells. This study illuminated how PEF can affect TCS biodegradation and gives insights into the application prospect of electrochemical-assisted biodegradation technology in water environment treatment